Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Kelas VIII MTs An Najahiyyah Tahun Pelajaran 2025/2026 - Ralda Auril Trissanda; Shendy Andrie Wijaya; David K. Susilo (Universitas Hamzanwadi, 2025)
This study was motivated by the fact that the learning model currently being used has not contributed to the learning outcomes of eighth grade students. Specifically, when students study social studies, they have not maximized their ability to express ideas to solve problems through analytical questions. The purpose of this study is to analyze the effect of the problem-based learning (PBL) model on the learning outcomes of eighth-grade students at MTs An Najahiyyah in the 2025/2026 academic year. The experimental research method with Paired Sample t-test analysis was used to measure the difference in the effect of a treatment on the same sample, namely eighth grade with 33 students. Data collection was conducted through observation and tests. The instruments were tested for validity and reliability. From the results of the Paired Sample t-test analysis, the tcount value was > than the ttable, namely 8.120 > 2.021, and the significance value was < than alpha 5% (0.000 < 0.05), so it can be said that H0 was rejected and Ha was accepted. This shows that there is an effect of the problem-based learning (PBL) model on the learning outcomes of eighth-grade students at MTs An Najahiyyah in the 2025/2026 academic year. Referring to these results, the use of the PBL model is in line with its advantages, namely that PBL directly trains students to solve problems, both those in the subject matter and those relevant to real life